Implementation of Design and Social Media Strategies to Increase Kopi Ngaso Followers - Rio Dody Christanto; Suprayitno Suprayitno (Jurnal Syntax Admiration, 2025)
Small businesses like Kopi Ngaso often struggle with inconsistent social media branding, limiting their digital reach. This study examines how structured internships can optimize design and content strategies to address this gap. The research objectives are to (1) strengthen Kopi Ngaso’s brand identity through visual consistency, (2) improve social media engagement via planned content, and (3) evaluate the internship model’s dual benefits for students and businesses. The research used a mixed-method approach included SWOT analysis, content calendar implementation, and performance tracking. Students collaborated on design (Canva) and platform (Instagram/TikTok) optimization. The strategy increased followers by 45%, enhanced customer interaction, and established a cohesive brand aesthetic. Interns gained practical skills in digital marketing. The study highlights the value of integrating academic training with real-world UMKM needs, offering a scalable model for similar businesses. Future research could explore long-term loyalty effects and AI tools for efficiency.